2020
DOI: 10.1080/1028415x.2020.1829344
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol improves mitochondrial energetics of a cellular model of Alzheimer’s disease

Abstract: Mitochondrial energetic deficit is one of the hallmarks of neurodegenerative disorders, e.g. Alzheimer´s disease (AD). Adherence to a Mediterranean diet is associated with lower incidence of cognitive decline and AD and extra virgin olive oil's (poly)phenols such as oleuropein and hydroxytyrosol (HT) are being actively studied in this respect. In this study, we assessed the effects of HT on mitochondrial energetic dysfunction in the 7PA2 cells cellular model, i.e. one of the best cellular models of Aβ toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…As mentioned in the Section 5 , mitochondrial energetic deficit and altered energy metabolism are features of AD, and it turns out that HTyr is able to acutely induce mitochondria generation and fusion, in a model of Aβ toxicity and mitochondrial dysfunction (cell line 7PA2) [ 139 ]. Moreover, it has been shown that OLE and HTyr activate autophagy in SH-SY5Y cells exposed to toxic Aβ1–42 oligomers, thus preventing the accumulation of ROS and the impairment of mitochondrial function [ 140 ].…”
Section: Neuroprotective Function Of Htyr and Ole In Neurodegenerativ...mentioning
confidence: 99%
“…As mentioned in the Section 5 , mitochondrial energetic deficit and altered energy metabolism are features of AD, and it turns out that HTyr is able to acutely induce mitochondria generation and fusion, in a model of Aβ toxicity and mitochondrial dysfunction (cell line 7PA2) [ 139 ]. Moreover, it has been shown that OLE and HTyr activate autophagy in SH-SY5Y cells exposed to toxic Aβ1–42 oligomers, thus preventing the accumulation of ROS and the impairment of mitochondrial function [ 140 ].…”
Section: Neuroprotective Function Of Htyr and Ole In Neurodegenerativ...mentioning
confidence: 99%
“…The dietary administration of hydroxytyrosol was shown to promote the activity of mitochondria and reestablish the deficit of energy in the 7PA2 cell model of Alzheimer’s disease [ 169 ]. Likewise, González-Correa et al [ 170 ] reported that the supplementation of hydroxytyrosol also reduces the number of retinal ganglion cells in streptozotocin-diabetic rats.…”
Section: Antioxidants In Diseases: General Evidencementioning
confidence: 99%
“…As far as we know, mitochondrial dysfunction is one of the key cellular hallmarks of neurodegenerative diseases [246]. In the 7PA2 cell cellular model simulating Aβ toxicity of AD, hydroxytyrosol can restore the energy deficiency to maintain mitochondrial function [247]. Meanwhile, hydroxytyrosol ameliorates the neuronal impairment in APP/PS1 mice via modulating mitochondrial oxidative stress, neuroinflammation, and apoptosis [248].…”
Section: Hydroxytyrosolmentioning
confidence: 99%